Introduction - Picking up the splinters of history: images of Latin America, the Caribbeans and Africa in contemporary fiction - Javangwe, Tasiyana D.; Chitando, Anna (Unisa Press, 2016)
The Barbadian poet Edward Kamau Brathwaite, though referring to the Caribbean situation, captures the critical challenge that confronts the artist of the global south when he poses the question, “How does the artist work and function in a plurally fragmented world9" (Brathwaite, 1970: 34). The pernicious legacy of slavery, colonialism and the neo-colonial order in Latin America, the Caribbeans and Africa left multiple fractures in these communities that have elicited equally multiple and complex responses from artists trying to make meaning of existence.